APLIKASI PENGOLAHAN DATA RENTAL DVD TIGA SAUDARA DI MUARO JAMBI - Fery Purnama (JURNAL AKADEMIKA)
Most leasing or rental DVD in Indonesia, particularly in the city of Jambi still using manual systems are still using a notebook written by hand, while the era of technology and growing rapidly so that attract buyers and simplify the way power works fast and orderly. Such as processing applications rental DVD Three brothers in Muaro still using manual systems with a notebook. The system used is also often difficult for employees to perform lending services to the customers, especially during rush hour. In addition, the DVD rental Three Brothers employees tend to have difficulty in making reports per day. Based on these problems, the manager of the rental requires a lending transaction applications that can assist managers in conducting a transaction or payment process and facilitate the preparation of reports intake per day. Therefore in completing this practical work made a Application Processing Rental DVD Tiga Saudara Muaro Jambi.